The Patriotic Associations And Their Activity After The Agreement Of Mudros - Malkhasyan, Silvart (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
After the Armistice of Mudros was signed between the Ottoman State and the Allied Powers on October 30, 1918, Constantinople was filled with Armenian orphans, widows, and deportees. The Armenian community established or revived various aid associations and institutions to heal their wounds. Such were the patriotic associations whose success would be helped by all community classes. The mentioned associations had branches both in the province and abroad. They would morally and materially support their compatriots and work to restore their province by repairing buildings. Patriotic associations continued their activity until 1922. When, due to new political conditions, Armenians began to migrate from Constantinople, the patriotic associations’ activity ended.
Keywords: History